Impact of Biostimulants on the Growth Dynamics and Developmental Performance of Calves - Ibragimov , Dr. Ahmad Tulqinovich; Isometdinov, Azizjon Parvizovich (American Journal of Biomedicine and Pharmacy, 2025)
This article presents literature data on the effects of biostimulants on young animals and provides a detailed analysis. The impact of biostimulants on calves is studied, and their effects are highlighted, including changes in body temperature, heart rate, respiration rate, and live weight gain. The relevance of the topic is substantiated. Modern research methods are presented, and calf live weight is measured using electronic scales using modern methods. The purpose and objectives of the study are stated. The article also contains conclusions and a list of references.